The effect of good corporate governance on tax avoidance - Amelia Ivon Oktavia; Siti Nurlaela; Purnama Siddi (Faculty of Economics and Business Mulawarman University, 2021)
This study aims to determine the effect of corporate governance on tax avoidance of property companies listed in the Indonesia Stock Exchange. This research is a quantitative descriptive study. The population in this study was obtained from the Indonesia Stock Exchange website www.idx .go.id, amounting to 48 1jsted companies, the type of data used in this study is secondaryidata. The data collection technique used in this research is documentation1j. Data analysis in this studyiincludes multiple lineariregression analysist, t test, and the coefficient of determination1j. The results showed that: The variable of institutional ownership, the number of commissioners and the percentage of independent commissioners did not have a sign1jicant effect on tax avoidance, with a negative coefficient, and the variable number of audit committees had no significant effect on tax avoidance, with a positive coefficient.